2020
DOI: 10.1089/apc.2019.0288
|View full text |Cite
|
Sign up to set email alerts
|

Unlocking HIV Pre-Exposure Prophylaxis Delivery: Examining the Role of HIV Providers in Pre-Exposure Prophylaxis Care

Abstract: Despite being a promising prevention strategy for populations at risk for HIV acquisition, there has not been rapid uptake of HIV antiretroviral pre-exposure prophylaxis (PrEP). Yet, HIV clinics within the Mount Sinai Health System in New York City have successfully incorporated PrEP. HIV care providers (n = 18), who practice in these clinics and were early PrEP adopters, participated in a survey and semistructured interview. Qualitative thematic analysis revealed that barriers and facilitators to PrEP uptake … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 17 publications
1
3
0
Order By: Relevance
“…Our study revealed that almost a third of participants did not include HIV PrEP service in general service points. This is similar to studies that were conducted by Kenison et al [30] and Muwonge et al, [26] which revealed that poor practices of PrEP delivery are demonstrated by referring patients requiring HIV PrEP prescriptions to other health providers who are stationed at different service…”
Section: Researchsupporting
confidence: 89%
“…Our study revealed that almost a third of participants did not include HIV PrEP service in general service points. This is similar to studies that were conducted by Kenison et al [30] and Muwonge et al, [26] which revealed that poor practices of PrEP delivery are demonstrated by referring patients requiring HIV PrEP prescriptions to other health providers who are stationed at different service…”
Section: Researchsupporting
confidence: 89%
“…In the final model, after adjusting for other covariates being male is associated with a 1.77 times higher risk of getting lost as compared to being female (ARR=1.770, 95% CI =1.120, 2.797). In addition, the risk of getting lost from PrEP follow-up youngest (21–30) years was 0.406 times lower than those aged (51–60) years (ARR=0.406, 95% CI =0.223, 0.738, P-value=0.003). similarly, those in the age of (31–40) years was associated with a 1.77 times risk of loss compared with (51–60) years (ARR= 0.391, 0.641 Vs. 1.77 95% CI).…”
Section: Resultsmentioning
confidence: 94%
“…High adherences is especially important among male, as compared to women using PrEP, to achieve high efficacy of PrEP because of differences in perception and health seeking behavior (20). Approach based on their gender during initiation of PrEP and during their follow up time based on their needs, Providers' suggestion and support of PrEP use have also been suggested as effective solutions to improve retention in PrEP care in a variety of diverse situations (21,22). This study shows that PrEP patients are at high risk of loss to follow-up at the early stage of PrEP initiation was 1.815 times LTFU the incidence who didn't have frist follow up visit).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation